RNA editing in response to COVID-19 vaccines: unveiling dynamic epigenetic regulation of host immunity - Jin, Yun-Yun; Liang, Ya-Ping; Pan, Jia-Qi; Huang, Wen-Hao; Feng, Yan-Meng; Sui, Wei-Jia; Yu, Han; Tang, Xiao-Dan; Zhu, Lin; Chen, Jian-Huan (Frontiers in Immunology, 2024)
Background: COVID-19 vaccines are crucial for reducing the threat and burden of the pandemic on global public health, yet the epigenetic, especially RNA editing in response to the vaccines remains unelucidated. Results: Our current study performed an epitranscriptomic analysis of RNA-Seq data of 260 blood samples from 102 healthy and SARS-CoV-2 naïve individuals receiving different doses of the COVID-19 vaccine and revealed dynamic, transcriptome-wide adenosine to inosine (A-to-I) RNA editing changes in response to COVID-19 vaccines (RNA editing in response to COVID-19 vaccines). 5592 differential RNA editing (DRE) sites in 1820 genes were identified, with most of them showing up-regulated RNA editing and correlated with increased expression of edited genes. These deferentially edited genes were primarily involved in immune- and virus-related gene functions and pathways. Differential ADAR expression probably contributed to RNA editing in response to COVID-19 vaccines. One of the most significant DRE in RNA editing in response to COVID-19 vaccines was in apolipoprotein L6 (APOL6) 3' UTR, which positively correlated with its up-regulated expression. In addition, recoded key antiviral and immune-related proteins such as IFI30 and GBP1 recoded by missense editing was observed as an essential component of RNA editing in response to COVID-19 vaccines. Furthermore, both RNA editing in response to COVID-19 vaccines and its functions dynamically depended on the number of vaccine doses. Conclusion: Our results thus underscored the potential impact of blood RNA editing in response to COVID-19 vaccines on the host’s molecular immune system.